The Impacts of the Political Uncertainty on the Currency Exchange Rate - Youness, Mohamad (Technium Social Sciences Journal, 2022)
This paper examines the impacts of political uncertainty on the currency exchange rate, taking the fluctuation of the LBP exchange rate against USD dollar in the black market as a practical case. It shed light on the most important political events and decisions that happened in Lebanon and the region during the period (2019-2021) and linked it directly to the currency exchange rate, to show the impacts of the political instability on the LBP/USD exchange rate. We depend on the daily observations of the LBP exchange rate in the central bank and black market to perform empirical tests and regression models and we gathered the political events and news from the National News Agency (NNA). The results show that political uncertainty and instability have a direct impact on the currency exchange rate.